Use of thermal gradients for control of vortex matter in mesoscopic superconductors - Duarte, E. C.S. [UNESP]; Presotto, A. [UNESP]; Okimoto, D. [UNESP]; Souto, V. S. [UNESP]; Sardella, E. [UNESP]; Zadorosny, R. [UNESP] (IOP Publishing, 2019)
Usually, the measurements of electronic and magnetic properties of superconducting samples are carried out under a constant temperature bath. On the other hand, thermal gradients induce local variation of the superconducting order parameter, and the vortex dynamics can present interesting behaviors. In this work, we solved the time-dependent Ginzburg-Landau equations simulating samples under two different thermal gradients, and considering two values of the Ginzburg-Landau parameter, κ. We find that both parameters, i.e. κ and thermal gradients, play an important role on the vortex dynamics and on the magnetization behavior of the samples.
Keywords: mesoscopic superconductor; thermal gradient; time-dependent Ginzburg-Landau; vortex states